Evaluasi Program KDII (Konsep Dasar Ilmu Islam) Menggunakan Model CIPP - Hudayani, Fiqrah; Syamsudduha, St. (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic education based on the Koran and Sunnah of the Prophet plays a role in shaping the character and faith of the younger generation. The Basic Concepts of Islamic Science (KDII) program at the Le Natural Sciences School aims to strengthen students' Islamic scientific foundation, foster a love of the Koran, and prepare them as future leaders. This research evaluates the KDII program using the CIPP (Context, Input, Process, Product) model to assess its effectiveness and impact. This research method is a case study with a qualitative approach at Le Scholar Boarding School. The evaluation results show that the KDII program has succeeded in increasing students' understanding of the basic teachings of Islam and helping them apply Islamic values in their daily lives. This shows the success of the program in forming students who have noble character and are ready to make a positive contribution to society.